If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -15 + 3c + -7c = -43 Combine like terms: 3c + -7c = -4c -15 + -4c = -43 Solving -15 + -4c = -43 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + -4c = -43 + 15 Combine like terms: -15 + 15 = 0 0 + -4c = -43 + 15 -4c = -43 + 15 Combine like terms: -43 + 15 = -28 -4c = -28 Divide each side by '-4'. c = 7 Simplifying c = 7
| log(2x+1)log(2x-1)=1 | | 10=-7v+4(v+4) | | log(2x-12)=4 | | 2d+8=32 | | 4x-3+3=1+3 | | -9x+45-10+x=35 | | 2x+22=4x+13 | | -10z-5z=45 | | 3k+4=23 | | -5a+13a=64 | | 26.55=4x+18.75 | | 16/9=8x | | 3-2y=15 | | K=1+3.3log(17) | | 7=-6x-5 | | x-5=3x+2whatisx | | 1=21 | | y=-6(4)+24 | | -15c/-4 | | 3(-6x+24)-x+4=0 | | -0.5(5x-2)=-3(0.5x-2)-1 | | 453.6672=(3.14*r^2)+(3.14*r^2)+(13*r*6.28) | | 5.7x-5=3(x-0.7)-11 | | 0.3(0.1-0.5)=1.2 | | y/3-7=-5 | | 0.6(2x-1)=0.4x-1.4 | | 25.748=(3.14*r^2)+(3.14*r^2)+(3.1*r*6.28) | | 2x^2-12+8=0 | | 0.2(x+1)=1.8 | | 0.3x+1.4=0.6x-1 | | 3x^3*4= | | 0.2x+1.9=-x+4.3 |